Evaluation of medical examination of forensic medicine specialists during / after detention within the scope of Istanbul Protocol - Keten, Alper; Abacı, Ramazan (Journal of forensic and legal medicine, 2020)
Introduction: The Istanbul Protocol is a document prepared by many scientists from different countries and accepted by the United Nations thematising the medical reporting of torture. Normally, forensic specialists are responsible for medical examinations of torture victims, but this study looks at forensic specialists who were themselves subject to torture and mistreatment. It aims to analyze and evaluate, especially with regard to the Istanbul Protocol, the medical examinations performed on them while they were in detention. Material/method: This study includes experts in forensic science who were detained during and after the state of emergency that was declared in 2016 in Turkey. Participants were asked questions regarding the examination steps specified in the Istanbul protocol. The Google Forms system (Google Inc., CA/USA) was used for the surveys, sent to the participants via text message. Results: Twenty-two forensic scientists who were detained during and after the state of emergency in Turkey participated in this study. 45.5% of the participants were not asked for identification before their medical examination in detention. 36.4% of the participants stated that police were present in the examination room. Only 13.6% of participants found the privacy conditions during the examination appropriate. 90.9% stated that the time allocated for the examination was insufficient. The medical examinations lasted from 10 s to 10 min. Most participants were examined in less than 5 min. When asked if they were abused, 22.7% stated that they were not tortured, and 77.3% stated that they were subjected to torture or mistreatment practices, such as beatings, inappropriate use of handcuffs, being forced to wait or being rushed unnecessarily, being abandoned in isolating or hostile environments. In addition, the questions required to assess the psychological indications of torture and maltreatment were never asked in 40.9% of the cases. Discussion and conclusion: Although torture is prohibited by international and humanitarian law, it has not completely disappeared. Medical personnel play an important role in torture assesment and prevention. The testimony of the forensic experts, who were fired and detained, revealed that the medical examinations during and after the State of Emergency in Turkey did not comply with the Istanbul Protocol and ethical rules. Medical examinations not carried out in accordance with the Istanbul Protocol lead to the denial of many rights and health problems. A worldwide awareness and sensitivity is needed to solve this problem.
Gesehen am 22.06.2020